Community Capacity Building through an Alternative Approach Based on Participation in Handling Dengue Hemorrhagic Fever (DHF) in Semarang - Isnu Putra Pratama; Wiwandari Handayani; Jawoto Sih Setyono; Nyoman Prayoga (Journal of Regional and City Planning, 2017)
Abstract. Indonesia became the country with the highest number dengue cases in Asia, with as many as 80.065 cases, according to data by the United Nations in 2010. Dengue fever has killed hundreds, posing a threat to society against vector-based diseases, especially to those who are vulnerable to the impacts of climate change. The vulnerability of society will depend on their adaptive capacity in preventing or responding to an increased risk of disease transmission. In the efforts to increase resistance to the dengue risk, it will be difficult when only relying on increasing the quality of human resources in the health sector. In this context, the overall participation of the communities who are vulnerable of dengue becomes significant. DHF prevention programs with an alternative approach based on community participation in the ACTIVE (Actions Changing The Incidence of Vector- Borne Endemic Diseases) program in Semarang have been carried out by Mercy Corps Indonesia (MCI) with the Government of Semarang (Health Department, Development Planning Agency, Meteorology Climatology and Geophysics Agency, Department of Education) as well as academics of Diponegoro University. A series of activities in the ACTIVE program aims to build a city resilient to climate change, especially in the health sector by reducing the incidence of dengue. This paper aims to assess an alternative approach based on participation implemented through the concept of community capacity building within the framework of ACTIVE Program. The method used is descriptive analysis with a qualitative approach to the process of community capacity building. An alternative approach based on the concept of social learning and inclusive planning is able to get the government's attention and arouse the enthusiasm and the spirit of the community facing dengue in the region. Based on interviews with stakeholders, they generally refer to the alternative approach based on participation as interesting and consider the approaches effective in solving the problems of dengue at the level of public behavior. Keywords. Dengue hemorrhagic fever, ACTIVE, alternative approach, community capacity.Abstrak. Indonesia menjadi negara dengan kasus Demam Berdarah Dengue (DBD) tertinggi di Asia  yaitu sebanyak 80.065 jiwa (United Nation, 2010). Wabah DBD telah menelan banyak korban jiwa sehingga menimbulkan ancaman bagi masyarakat terhadap penyakit berbasis vektor, terlebih mereka yang rentan di bawah tekanan dampak perubahan iklim. Kerentanan masyarakat akan tergantung pada kapasitas adaptif dalam mencegah atau merespon risiko peningkatan transmisi penyakit. Dalam melakukan upaya peningkatan ketahanan terhadap risiko DBD tersebut, maka akan sulit jika hanya mengandalkan peningkatan kualitas SDM di bidang kesehatan saja. Pada konteks ini, maka partisipasi menyeluruh dari masyarakat yang rentan terhadap DBD menjadi signifikan. Program penanggulangan DBD dengan pendekatan alternatif berbasis partisipasi masyarakat dalam kegiatan ACTIVE (Actions Changing The Incidence of Vector- Borne Endemic Diseases/Inisiatif Penanganan Penyakit Endemik Berbasis Vektor) di Kota Semarang telah dilakukan oleh Mercy Corps Indonesia (MCI) bersama dengan Pemerintah Kota Semarang (Dinas Kesehatan, Badan Perencanaan dan Pembangunan Daerah (Bappeda), Badan Meteorologi, Klimatologi dan Geofisika (BMKG), Dinas Pendidikan) serta Universitas Diponegoro selaku akademisi. Rangkaian kegiatan dalam Program ACTIVE bertujuan untuk membangun kota yang berketahanan terhadap perubahan iklim khususnya dari sektor kesehatan dengan cara mengurangi kejadian DBD. Tulisan ini bertujuan untuk meninjau pendekatan alternatif berbasis partisipasi yang diterapkan melalui konsep peningkatan kapasitas masyarakat dalam kerangka Program ACTIVE. Metode yang digunakan adalah analisis deskriptif dengan pendekatan kualitatif terhadap proses peningkatan kapasitas masyarakat. Pendekatan alternatif berdasarkan konsep pembelajaran sosial dan perencanaan inklusif mampu mendapatkan perhatian pemerintah dan menggugah antusiasme serta semangat masyarakat dalam menghadapi DBD di wilayahnya. Berdasarkan hasil wawancara para stakeholder, umumnya menyinggung pendekatan alternatif berbasis partisipasi yang menarik dan dinilai efektif dalam menyelesaikan permasalahan DBD pada tingkat perilaku masyarakat.Kata kunci. demam berdarah dengue, ACTIVE, pendekatan alternatif, kapasitas masyarakat.